PERSEPSI PEGAWAI TERHADAP IMPLEMENTASI MANAJEMEN TALENTA DI ORGANISASI PEMERINTAHAN - Ahmad Rifai; M. Syamsul Maarif; Anggraini Sukmawati (School of Business, Bogor Agricultural University (SB-IPB), 2021)
This study aims to analyze employee perceptions of the implementation of talent management in the Ministry of Finance, as well as to analyze the relationship between the profile of respondents and the four stages of talent management. The population in this study was 80,996 employees within the Ministry of Finance and the sample size was 408 employees who were determined by using stratified random sampling technique. Data analysis using a quantitative approach includes validity and reliability tests, averaging, two boxes, cross tabulation, and different tests. The results showed that employees' perceptions of the implementation of talent management at the Ministry of Finance were good, but improvements were needed in 7 indicators: (1) understanding of the 9 boxes for mapping employees, (2) searching for talented people by organizations, (3) information criteria to become talent, (4) information about employees who are determined to be talents, (5) motivation of leaders to develop employee careers, (6) objective assessment of career development, and (7) facilities for employee competency development programs. There is a relationship between respondents and these 7 indicators. Meanwhile, there are differences in respondents' perceptions with these 7 indicators. The managerial implications that can be applied are the socialization of talent management to all employees, employee development programs to improve competence and careers, and paying attention to the profile of respondents in developing talent management. Keywords: career development, competency, manpower planning, Ministry of Finance, talent mapping